Mapping breast cancer research in Malaysia: a scientometric analysis - Tengku Muhammad Hanis,; Juhara Haron,; Wan Faiziah Wan Abdul Rahman,; Wan Nor Arifin,; Nur Intan Raihana Ruhaiyem,; Rosni Abdullah,; Kamarul Imran Musa, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
The purpose of this study was to provide an overview of breast cancer researches in Malaysia. Besides, this study aimed to identify the trends of breast cancer research in Malaysia. This study retrieved 343 related publications from the Scopus database. After removing one duplicated publication and another two publications that did not meet the study criteria, the remaining 340 publications were analysed using a bibliometric analysis and trending keywords analysis. This study found that the annual growth rate of publications was 7.4%. The majority of the publications were research articles and multi-author. The most productive author was Yip CH with 69 publications, and the University of Malaya was the top institution in Malaysia related to this research area. For the last five years, there were no dominant themes in this research area. However, this study found two emerging clusters of breast cancer research in Malaysia, which related to medical data analytics and precision medicine in genomic breast cancer. Overall, breast cancer research in Malaysia is progressing towards a positive side, though a few improvements are needed. As the funding in this research area is scarce, proper allocation of the resources is needed.